AUTHENTICITY AND POWER: RECONNECTING WITH MARGINALIZED ASPECTS OF THE FEMININE - Mutschler, Julia Fânzeres Caminha; Silva, Lisienne de Morais Navarro Gonçalves (Seven Editora, 2025)
The present study aims to provide a critical analysis of the historical marginalization of the three feminine powers — cyclicity, ancestry, and sexuality — and their impact on female subjectivity, as they directly influence the construction of women’s identity, self-esteem, and autonomy. The central question of this research is: How does the historical marginalization of cyclicity, ancestry, and sexuality affect the construction of women’s identity, self-esteem, and autonomy, and in what ways can the conscious integration of these three powers promote empowerment and authenticity? The hypothesis that supports this study is that, through self-knowledge, women achieve authenticity and liberation in the process of self-occupation by re-signifying individual and collective experiences. To substantiate the critical analysis, the theoretical concepts of Audre Lorde (2019), who problematizes power as erotic and self-expression as resistance, are used; Brené Brown (2019), who discusses vulnerability and courage; Chimamanda Ngozi Adichie (2014), with her contributions on the danger of a single story, feminism, and the social construction of femininity; Clarissa Pinkola Estés (1992), on ancestral archetypal feminine wisdom; Michel Foucault (1983; 1986), on biopower and subjectivation; Silvia Lane (1999), from the perspective of critical social psychology; and Zygmunt Bauman (2001), in his reflections on identity in liquid modernity. This bibliographic research seeks to integrate these authors to broaden the understanding of the phenomenon, highlighting how the conscious reclaiming of these three powers can serve as a path to personal and social transformation. The analysis aims to demonstrate that self-occupation — understood as the capacity to recognize oneself and lead one’s own life — is strengthened when women reconnect with their ancestry, embrace their natural cycles, and express their sexuality and creativity.DOI: https://doi.org/10.56238/sevened2025.036-027